Leadership for learning : how to help teachers succeed - Glickman, Carl D. (Alexandria, Va. : Association for Supervision and Curriculum Development, 2002)
Offers advice to instructional leaders on how to best work with teachers to improve classroom teaching and learning, describing different methods of classroom assistance, formats for observations, and approaches to working directly with teachers.
Looking at classroom teaching and learning -- Structures for classroom assistance -- Formats for focusing observation -- Approaches to working closely with teachers -- Direct applications to assisting teachers -- Criteria for assessing teacher competence and growth -- Purpose, strength, and collegial force for school success.
"ASCD product no. 101031"--T.p. verso.
Includes bibliographical references and index.
Professional
Keywords: Effective teaching -- United States; School supervision -- United States; Teacher effectiveness -- United States; School supervision; Teachers -- United States; Teaching -- United States